2010
DOI: 10.1093/jmt/47.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy CD Creation for Initial Pediatric Radiation Therapy: A Mixed Methods Analysis

Abstract: A mixed methods research design was used to investigate the effects of a music therapy CD (MTCD) creation intervention on pediatric oncology patients' distress and coping during their first radiation therapy treatment. The music therapy method involved children creating a music CD using interactive computer-based music software, which was "remixed" by the music therapist-researcher to extend the musical material. Eleven pediatric radiation therapy outpatients aged 6 to 13 years were randomly assigned to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 0 publications
0
71
0
10
Order By: Relevance
“…The choice was justified by being a song used in other studies with positive results, such as: decreased stress, sense of vitality and improvement in heart rate variability, encouraging relaxation, effects expected by the researchers. 13 Regarding the music, the recommended music to provide sensations of comfort and tranquility are those structured with slow rhythms, melodies with bass and gentle intensity that promote the reduction of heart and respiratory rate, while music with high tones and fast rhythms increase vital parameters and influence the individual's alertness. 20 However, in the American study in a hospital in North Carolina, the researchers observed that some participants did not achieve the expected result because they reacted with discontent due to the fact that they were listening to unknown music.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The choice was justified by being a song used in other studies with positive results, such as: decreased stress, sense of vitality and improvement in heart rate variability, encouraging relaxation, effects expected by the researchers. 13 Regarding the music, the recommended music to provide sensations of comfort and tranquility are those structured with slow rhythms, melodies with bass and gentle intensity that promote the reduction of heart and respiratory rate, while music with high tones and fast rhythms increase vital parameters and influence the individual's alertness. 20 However, in the American study in a hospital in North Carolina, the researchers observed that some participants did not achieve the expected result because they reacted with discontent due to the fact that they were listening to unknown music.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, corroborating studies that address the importance of musical preference, the researchers suggested that pediatric patients should choose the music for their well-being and for positive effects in musical intervention. 13 The studies also showed limitations in musical intervention, methods and the materials used. Although they have identified the measures and how the music was played, there are situations that directly interfere with the effects generated by the music, for example, the use of headphones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Les analyses effectuées n'ont pas rapporté d'effet significatif suite aux interventions sur (Pai, Drotar, Zebracki, Moore et Youngstrom, 2006;Richter et al, 2015) (Robb et al, 2014 ;Waldon, 1998) et deux études étaient strictement de nature qualitative (Aasgaard, 2001;O'Callaghan, Baron et Dun, 2011). Ces recherches ont montré que des séances de musicothérapie ont été en mesure de diminuer le niveau d'anxiété (Waldon, 1998), d'améliorer l'engagement actif du jeune dans son environnement (Barry, O'Callaghan, Wheeler et Grocke, 2010), d'améliorer l'état émotionnel (Barrera, Rykov et Doyle, 2002), d'améliorer le ressenti de soutien social reçu par les professionnels de la santé, la famille et les amis (Robb et al, 2014), d'entrainer un sentiment de plaisir et de réalisation (Aasgaard, 2001) ainsi que des effets positifs au sein même des familles des patients (O'Callaghan, Baron et Dun, 2011;Robb et al, 2014).…”
Section: Les Interventions Déjà Mises En Oeuvre Pour Traiter La Détreunclassified